Inhibition of Biogenic Amines Formation in Fermented Foods by the Addition of Cava Lees - Hernández-Macias, Salvador; Martín-Garcia, Alba; Ferrer-Bustins, Núria; Comas-Basté, Oriol; Riu-Aumatell, Montserrat; López-Tamames, Elvira; Jofré, Anna; Latorre-Moratalla, M. Luz; Bover-Cid, Sara; Vidal-Carou, M. Carmen (Frontiers in Microbiology, 2022)
Food safety can be compromised by some bioactive compounds such as biogenic amines that can be specially found in fermented foods due to the bacterial decarboxylation of some amino acids by fermentative or spoilage bacteria. Cava lees are a winery by-product rich in fiber and phenolic compounds and previous works have raised their revalorization from a food safety point of view. The aim of the current work was to investigate whether the use of cava lees can help to control biogenic amine formation in bread and fermented sausages. In bread, only very low levels of biogenic amines (putrescine, cadaverine, and/or spermidine) were found, whose content did not vary with the addition of different amounts of lees. However, the addition of lees in fermented sausages significantly reduced the formation of tyramine and cadaverine. In sausages spontaneously fermented and inoculated with Salmonella spp., the presence of cadaverine and putrescine diminished by 62 and 78%, respectively, due to the addition of cava lees. The addition of cava lees phenolic extract also showed an anti-aminogenic effect (21% for cadaverine and 40% for putrescine), although in a lesser extent than cava lees. Cava lees and their phenolic extract were shown to be an effective strategy to control the undesirable accumulation of high levels of biogenic amines during the production of fermented products.